El efecto de la inclusión financiera en el crecimiento económico: un análisis para países desarrollados y en vías de desarrollo - Ramírez Valdez, Camila Gabriela (2023)
This work aims to establish to what extent financial inclusion impacts the economic growth of developed and developing countries during the period from 2008 to 2019. A Generalized Method of Moments (GMM) model was used to explore the relationship of three representative dimensions of financial inclusion, through which it was found that an increase of 1% in the percentage of current loans could generate an average increase of 0.64% in the growth of GDP per capita, while the other variables had a negative and significant effect. This result was studied by means of two additional estimations with the quadratic terms of the variables banking penetration and availability of banking services. It was found that there is a negative effect generated as a consequence of a lower efficiency after a maximum threshold. The indicators studied prove to be significant for developing countries, since these have few banking services.